The Influence of Online Brand Community on Customers: A Case Study of A Multinational Motorcycle Company in Nepal - Gurung, Alin; Suwandee, Sasithorn; Suriyapa, Chairat; Suwandee, Suwat (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
Online brand community (OBC) played criticle role among motorcycle riders in Nepal who were so passionate about motorcycles since it allowed them to share and learn information as well as the experience among the members. The purposes of this study were as follows: 1) to explore the relationship among brand reputation, brand trust, and brand loyalty; and 2) to examine the relationship among OBC engagement, OBC attitude, brand trust, and brand loyalty. This study used a quantitative approach via self-administered questionnaire using the convenience sampling. They were distributed to customers who had accessed to online brand community (OBC) of the selected multinational motorcycle company in Nepal in 2023. The study included 297 respondents. The regression analysis and coefficients showed that product & services dimension (β=.176) of brand reputation has positive impact on brand trust, while social & environmental responsibility dimension (β=-259) of brand reputation has negative impact on brand trust. Furthermore, the study found that OBC engagement (β=-.126) has negative impact on OBC customer attitude; OBC customer attitude (β=.832) has positive impact on brand trust; and brand trust (β=.765) has positive statistically significantly impact on brand loyalty. The findings concluded that the company should focus on improving OBC customer attitude in order to increase brand trust, which also would enhance improvement on brand loyalty, thus, achieve their organizational objectives.